Comparable Subjective and Objective Clinical Outcomes After Fibular or Combined Tibial-Fibular–based Reconstruction of the Posterolateral Corner of the Knee: A Systematic Review and Meta-analysis. (December 2021) - Yeatts, Nicholas C.; Rao, Allison J.; Trofa, David P.; Hong, Ian S.; Moorman, Claude T.; Piasecki, Dana P.; Fleischli, James E.; Saltzman, Bryan M.
Abstract : Introduction: To compare subjective and objective outcomes of fibular and combined tibial-fibular (TF)-based posterolateral corner (PLC) reconstruction. Methods: A systematic review of literature reporting outcomes of posterolateral corner reconstruction was conducted including outcome studies of surgically treated PLC injuries with a minimum 1-year follow-up, postoperative subjective and objective outcomes including the patient-reported outcome scorings of Lysholm score, International Knee Documentation Committee evaluation (subjective and objective), dial test, and varus stress radiographs. Results: The 32 studies included comprised 40 cohorts: 12 cohorts (n = 350 knees) used a fibular-based technique, and 28 cohorts (n = 593 knees) used a combined TF-based technique. No statistically significant differences were found in patient-reported outcomes or objective clinical measurements comparing the two techniques using the Lysholm score ( P = 0.204, τ 2 = 3.46), International Knee Documentation Committee evaluation (subjective P = 0.21 τ 2 = 15.57; objective P = 0.398), dial test ( P = 0.69), or varus stress radiographs ( P = 0.98, τ 2 = 0.08). Conclusions: This study found no statistically significant differences in subjective or objective clinical outcome measurements after fibular-based versus combined TF-based PLC reconstruction. Further prospective evaluation comparing long-term clinical outcomes, complications, and surgical time may help to elucidate a preferred reconstructive technique.